Between reason and irrationality : the prose of Valerijan Pidmohylʹnyj - Tarnawsky, Maxim (University of Toronto Press, 1994)
Valerijan Pidmohyl'nyj (1901-1937) is one of the foremost Ukrainian writers of the twentieth century. His best work, Misto (The City), is arguably the finest novel in Ukrainian. Yet Pidmohyl'nyj is largely unknown even in Ukraine, where until recently his works were banned. Tarnawsky's aim is to bring Pidmohyl'nyj out of obscurity into the critical appreciation he deserves. This study takes a chronological approach to Pidmohyl'nyj's works, tracing his development as a writer along thematic, technical, and stylistic paths. Inspired by Western writers, especially the French realists, Pidmohyl'nyj evolves as a European intellectual in a Soviet Ukrainian setting. The texts are frequently cited in both the original Ukrainian and an English translation.